PREPARATION OF ACTIVATED CARBONS FROM DATE STONES BY CHEMICAL ACTIVATION METHOD USING FeCl3 and ZnCl2 as ACTIVATING AGENTS (Journal of Engineering, 2011)
Date stones were used as precursor for the preparation of activated carbons by chemicalactivation with ferric chloride and zinc chloride. The effects of operating conditions representedby the activation time, activation temperature, and impregnation ratio on the yield and adsorptioncapacity towards methylene blue (MB) of prepared activated carbon by ferric chloride activation(FAC) and zinc chloride activation (ZAC) were studied. For FAC, an optimum conditions of 1.25h activation time, 700 °C activation temperature, and 1.5 impregnation ratio gave 185.15 mg/gMB uptake and 47.08 % yield, while for ZAC, 240.77 mg/g MB uptake and 40.46 % yield wereobtained at the optimum conditions of 1.25 h activation time, 500 °C activation temperature, and2 impregnation ratio. The equilibrium data for MB adsorption on prepared activated carbons atoptimum conditions were well represented by the Langmuir isotherm model, giving maximumMB uptake of 304.51 and 387.54 mg/g for FAC and ZAC, respectively. Also, the results showedthat the surface area and iodine number of activated carbon prepared by activation with ferricchloride at optimum conditions were 780.06 m2/g and 761.40 mg/g, respectively. While 1045.61m2/g surface area and 1008.86 mg/g iodine number were obtained for ZAC prepared at optimumconditions.